2013
DOI: 10.1080/15017419.2013.795912
|View full text |Cite
|
Sign up to set email alerts
|

Working with Individual Plans: users' perspectives on the challenges and conflicts of users' needs in health and social services

Abstract: In Norway, an Individual Plan (IP) is a statutory right and a tool for cooperation between the client in need of long-term, coordinated services and the public services. This study analyses the explicit needs of users, how the various actors in the IP process met these needs, as seen from the users' perspective, and, finally, how disability influenced the outcomes. Participants expressed physical, psychological and social needs. These needs were similar for persons with physical or psychiatric health condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Cancer research shows that formal caregivers do not practice IP, and three barriers to IP are identified: a) formal caregivers' knowledge about their duty to inform and facilitate IP, b) formal caregivers' knowledge about collaboration networks within care, and c) allocation of time to perform the necessary administrative work (Saegrov, 2015). Several researchers have made conclusions about barriers such as organizational constraints and staff's (lack of) competence (Hansen, 2007;Holum, 2012b;Langhammer et al, 2013;Lidal & Røhme, 2006). One study showed that the administrative level in municipalities is fairly involved, indicating management's low interest in IP work (Berven, Ludvigsen, Christensen, & Nilssen, 2013).…”
Section: Individual Planmentioning
confidence: 99%
“…Cancer research shows that formal caregivers do not practice IP, and three barriers to IP are identified: a) formal caregivers' knowledge about their duty to inform and facilitate IP, b) formal caregivers' knowledge about collaboration networks within care, and c) allocation of time to perform the necessary administrative work (Saegrov, 2015). Several researchers have made conclusions about barriers such as organizational constraints and staff's (lack of) competence (Hansen, 2007;Holum, 2012b;Langhammer et al, 2013;Lidal & Røhme, 2006). One study showed that the administrative level in municipalities is fairly involved, indicating management's low interest in IP work (Berven, Ludvigsen, Christensen, & Nilssen, 2013).…”
Section: Individual Planmentioning
confidence: 99%